Refocus on Immunogenic Characteristics of Convalescent COVID-19 Challenged by Prototype SARS-CoV-2 - Xiaorong Huang; Chumin Liang; Manman Li; Huimin Chen; Zhaowan Li; Qianqian Ruan; Ximing Hu; Lilian Zeng; Huifang Lin; Wei Zhao; Jianpeng Xiao; Limei Sun; et al. (Vaccines, 2023)
Background: Mass basic and booster immunization programs effectively contained the spread of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus, also known as COVID-19. However, the emerging Variants of Concern (VOCs) of COVID-19 evade the immune protection of the vaccine and increase the risk of reinfection. Methods: Serum antibodies of 384 COVID-19 cases recovered from SARS-CoV-2 infection were examined. Correlations between clinical symptoms and antibodies against VOCs were analyzed. Result: All 384 cases (aged 43, range 1–90) were from 15 cities of Guangdong, China. The specific IgA, IgG, and IgM antibodies could be detected within 4–6 weeks after infection. A broad cross-reaction between SARS-CoV-2 and Severe Acute Respiratory Syndrome Coronavirus, but not with Middle East Respiratory Syndrome Coronavirus was found. The titers of neutralization antibodies (NAbs) were significantly correlated with IgG (r = 0.667, p < 0.001), but showed poor neutralizing effects against VOCs. Age, fever, and hormone therapy were independent risk factors for NAbs titers reduction against VOCs. Conclusion: Humoral immunity antibodies from the original strain of COVID-19 showed weak neutralization effects against VOCs, and decreased neutralizing ability was associated with initial age, fever, and hormone therapy, which hindered the effects of the COVID-19 vaccine developed from the SARS-CoV-2 prototype virus.